Modelling Value Selected Papers of the 1st International Conference on Value Chain Management - Jodlbauer, Herbert; Olhager, Jan.; Schonberger, Richard J.; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2012)
The publication contains a selection of the best double-blind reviewed papers presented, discussed and revised by participants of the 1st International Conference on Value Chain Management in Austria, Steyr, May 2011. The Value Chain Management (VCM) Conference presents scientific insights relevant to management as well as their translation into the practice of management. The conference focus is on the demand chain i.e. sales, production, purchasing, logistics, performance measurement and customer value management. The authors present analytical and conceptual articles as well as empirical studies showing multidisciplinary and intercultural approaches towards solving relevant open problems.
Keynotes -- Best Paper -- Searching for Value: Creating Value -- Value Chain Models: Decision-Making -- Value Chain Models: Complexity -- Value Chain Models: Lean Value Chains -- Value Chain Models: Supply and Value Chains -- Real World Implementations.
Keywords: Marketing; Industrial procurement; Production management; Operations research; Decision making; Marketing; Procurement; Operations Management; Operations Research/Decision Theory